Geography and economy of the Kaliningrad region: limitations and prospects of development - Sebentsov Alexander; Zotova Maria (Балтийский регион, 2013)
With its exclave status, the Kaliningrad region has been drawing attention of many researchers in different fields. Yet the prospects for cooperation between the region and neighbouring communities in Poland and Lithuania, which once constituted an integrated social, economic and political space, remain unclear. Media analysts and scholars alike tend to view the Kaliningrad region as “double periphery”, since it is excluded from major modernisation processes both in the European integration zone and in the Russian Federation. However, a detailed study involving polyscale socioeconomic indices, expert interviews, and surveys run contrary to this viewpoint. A look at the key indices of the Kaliningrad region and the neighbouring communities of Poland and Lithuania showed that both socioeconomic situation and standards of living are comparable in these areas, which indicates the prerequisites for mutually beneficial interregional cooperation. We have analysed factual information on socioeconomic development of cross-border regions and surveyed the students from the leading universities of Gdansk, Kaliningrad and Klaipeda. We were thus able to conclude that the reasons behind the delapidated cross-border relations are rather subjective and lie in the field of geopolitical orientation, information and institutional policy, as well as persistent stereotypes that shape public opinion. In this light, integration between the Kaliningrad region and mainland Russia is seen not only as an economic, but also as a sociocultural objective. An analysis of the stages of the region’s exclavisation, and policies of social support stemming from the uniqueness of the economic and geographical position of the region substantiate this conclusion.